Remappings of a Region: Popular Map Images Around and Beyond ‘Southeast Asia’ - Hera Hera (ITB Journal Publisher, DRPM ITB, 2023)
Our spatial understandings and perceptions are augmented by media representations of spaces. Whilst maps are often studied within the academic fields of geography and art history, their discussion within the context of design and design history remains insufficient. This paper delves into the study of popular maps as cross-cultural design artefacts. This is done through case studies from the perspective of graphic communication, analyzing maps along their symbolic, narrative, and discursive interpretations as well as how they interplay with lived experiences. The period from 1930s to the 1960s saw several events that led to frequent remappings of geo-entities around the loose assemblage of nations that we now know as Southeast Asia, which included the birth of new nations and the forging of alliances. This process of repeated remappings enables an interesting study on the nature of maps, their instrumentalization, and their consumption.